Vacillating images of Shin Saimdang: the invention of a historical heroine in colonial Korea. - Soojin, Kim (Inter-Asia Cultural Studies, 2014)
Shin Saimdang (1504–1551) is a nationally renowned historical figure who is generally considered an iconic traditional Korean woman; that is, “a wise mother and good wife” (hyeonmoyangcheo). Yet simultaneously, she is the most controversial woman in Korean history. In 2009, she became the first female figure to appear on a Korean banknote. Shin Saimdang is a truly complex symbol that has been (re)constructed as both a “tradition” and a figure in “the realm of memory” throughout the twentieth century in Korea. This paper examines the early phase of the discovery and interpretation of Shin Saimdang in the modern scene that began in the Enlightenment period and ended in the Japanese colonial period. In particular, the author highlights how frameworks and strategies to interpret Shin Saimdang vacillated according to nationalistic and colonial strategies. The author also explains how the concept of “good wife and wise mother” (ryousaikenbo in Japanese), which was imported from Japan, was hybridized and transformed into a complex ideal for Korean women that emphasized the “wise mother” over the “good wife.”